The value-added tax implications of a foreign-take-over of a South African resident VAT vendor with specific reference to patents registered in the name of the South African vendor - Van Zyl, Stephanus (University of Pretoria, 2025)
Mini Dissertation (LLM (Mercantile Law))--University of Pretoria, 2024.